Efficiency and Effectiveness of Olsera Based Financial Reporting in Café Total X - Kesuma, Leoni Virginia Lorainne; Ilham Pakawaru; Sugianto; Nina Yusnita Yamin (E-Jurnal Akuntansi, 2026)
Financial reporting remains a persistent challenge for many MSMEs, particularly in café businesses characterized by high transaction intensity and rapid cash turnover. This study analyzes the efficiency and effectiveness of financial reporting using the Olsera application at Café Total X. An interpretive qualitative approach was employed through observation, in-depth interviews, documentation review, and source triangulation. The Technology Acceptance Model (TAM) was used as a theoretical framework to examine perceived usefulness and perceived ease of use in the utilization of the Olsera application. The findings indicate that Olsera enhances efficiency through automated and integrated transaction recording, while effectiveness is reflected in the availability of timely, reliable, and decision-supportive financial information. User acceptance reinforces system sustainability and strengthens financial reporting quality in MSMEs.